The great leap backward: changes in the jumping performance of Australian children aged 11-12-years between 1985 and 2015 - Fraser, B. J.; Blizzard, L.; Tomkinson, G. R.; Lycett, K.; Wake, M.; Burgner, D.; Ranganathan, S.; Juonala, M.; Dwyer, T.; Venn, A. J.; Olds, T.; Magnussen, C. G. (Journal of Sports Sciences, 2019)
Previous data have indicated relative stability over time of paediatric jumping performance, but few data exist since the early 2000s. This study quantified the 30-year secular changes in jumping performance of Australian children aged 11-12-years using data from the Australian Schools Health and Fitness Survey (1985, n = 1967) and Growing Up in Australia`s Child Health CheckPoint (2015, n = 1765). Both cohorts measured jumping performance (standing long jump distance), anthropometric and demographic data. Secular changes in jumping performance means and quantiles were examined using multivariable linear and quantile regression. Between 1985 and 2015, jumping performance declined by 16.4 cm or by 11.2% (standardised change 0.66 SD, 95%CI 0.60 to 0.73). Adjustment for body mass reduced the effect by 32%, although the decline remained (absolute change - 11.1 cm, 95%CI -12.5 to -9.7; percent change 7.7%, 95%CI 6.7 to 8.6; standardised change 0.51 SD, 95%CI 0.44 to 0.57). This decline was evident across all quantiles. The jumping performance of Australian children aged 11-12-years has declined between 1985 and 2015, with body mass changes accounting for only part of the decline. Efforts should continue to promote paediatric muscular fitness, reduce adiposity, and aim to reverse this decline in jumping performance.